Sustainable development in perspective, definition, concepts and policy issues - Jaafar, Noraini (1992)
This paper examines the concept of sustainability with special emphasise on the context of sustainable development. The issues involved in defining the implicative meaning of sustainability is explored, and sustainability according to the ecological, economic and social perspectives are discussed. A brief outline of a sustainable development framework and the features of sustainable development is provided. Lastly, the paper presents some of the requirements to achieve sustainable development.